Nutritional support during the hospital stay is cost-effective for preventing adverse outcomes in patients with cancer - Schuetz, Philipp; Sulo, Suela; Walzer, Stefan; Krenberger, Sebastian; Brunton, Cory (Frontiers in Oncology, 2022)
Objective: Among cancer patients, malnutrition remains common and is a key challenge in oncology practice today. A prior study from our group revealed that malnourished cancer inpatients who got nutritional treatment (intervention group) had lower mortality and improved functional and quality of life outcomes compared to inpatients without nutritional support (control group). Our present analysis aimed to determine whether the improved patient recovery by nutritional support was paralleled by cost-effectiveness of this nutritional care. Methods: We examined hospital costs and health outcomes in cancer patients, using a Markov simulation model with daily cycles to analyze the economic impact of nutritional support in malnourished inpatients with malignancies. We compared results for a nutritional intervention group and a control group across a 30-day timeframe. Five health states were designated (malnourished but stable, complications, intensive care, discharge, death). Costs for the different health states were based on publicly available data for the Swiss medical system. Total patient cost categories included in-hospital nutrition, days spent in the normal ward, days in the intensive care unit, and medical complications. Results: Total per-patient costs for in-hospital supportive nutrition was just 129 Swiss francs (CHF). Across a 30-day post-admission interval, our model determined overall costs of care averaged 46,420 CHF per-patient in the intervention group versus CHF 43,711 in the control group—a difference of CHF 2,709 per patient. Modeled results showed a cost of CHF 1,788 to prevent one major complication, CHF 4,464 to prevent one day in the intensive care unit, and CHF 3,345 to prevent one death. Recovery benefits of nutritional care were thus paralleled by cost-effectiveness of this care. Conclusion: In-hospital nutritional support for oncology patients at malnutritional risk is a low-cost intervention that has both clinical and financial benefits.